2008
DOI: 10.1007/s12272-001-1270-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of morin on the imipenem-induced nephrotoxicity in rabbits

Abstract: The present study investigated the protective effect of morin, a natural flavonoid, on the imipenem-induced nephrotoxicity in rabbits. Nephrotoxicity of imipenem was examined after the intravenous administrations of imipenem (200 mg/kg) to rabbits in the presence and the absence of morin (12, 25, 50 mg/kg, p.o.). Cytotoxicity of imipenem was also examined in the presence and the absence of morin (100 microM) by using MDCK cells overexpressing human organic anion transporter 1 and 3 (MDCK/hOAT1 or MDCK/hOAT3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…All of these data suggest that flavonoids might protect against renal injury by inhibiting OAT1/OAT3‐mediated renal uptake of nephrotoxic drugs. The nephroprotective potential of morin was confirmed in animal studies: oral morin reduced the nephrotoxicity of intravenous imipenem (carbapenem antibiotic, OAT3 substrate) by inhibiting its OAT3‐mediated accumulation in the renal tubules …”
Section: Slc Transportersmentioning
confidence: 99%
“…All of these data suggest that flavonoids might protect against renal injury by inhibiting OAT1/OAT3‐mediated renal uptake of nephrotoxic drugs. The nephroprotective potential of morin was confirmed in animal studies: oral morin reduced the nephrotoxicity of intravenous imipenem (carbapenem antibiotic, OAT3 substrate) by inhibiting its OAT3‐mediated accumulation in the renal tubules …”
Section: Slc Transportersmentioning
confidence: 99%
“…It was also demonstrated that urinary excretion was the major route of elimination for REL, similar to what was observed for imipenem and cilastatin, providing rationale for characterizing the impact of renal impairment (RI) on the PK of REL and the IMI/REL combination. In addition, both REL and imipenem undergo active renal secretion and REL was shown to be a substrate of human organic anion transporter 3 (OAT3); therefore, it is important to determine if potential drug–drug interactions with probenecid, a prototypic OAT inhibitor, have an impact on exposure . In a previous PK study, coadministration of imipenem with probenecid resulted in a mild increase (15%) in drug exposure .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that flavonoids have the potential to limit the severity of drug-induced renal injury via the inhibition of OAT1. Lin et al [44] also reported that the flavonoid morin protected against imipenem-induced nephrotoxicity, via the inhibition of OAT3-mediated accumulation of this antibiotic. Alternatively, flavonoids may attenuate drug-induced renal damage via free radical scavenging [45,46] or anti-apoptotic M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 mechanisms [47].…”
Section: Discussionmentioning
confidence: 97%